Exploring the related factors of suicidal ideation in AIDS patients based on the interpersonal relationship theory of suicide - Jin, Xin; Peng, Tiecheng; Chen, Xiong; Chen, Juhai; Li, Jingjing; Wang, Yiyi (Revista de psiquiatria clínica, 2023)
Objective: To investigate, using the interpersonal relationship theory of suicide, the related factors of suicidal ideation in AIDS patients. Methods: The Infection Department of Guiyang Public Health Care Center's 300 outpatients and in patients with AIDS from September 2021 to July 2022 were chosen as the research subjects, and the general situation of AIDS patients' suicidal ideation was analyzed; The general data of AIDS patients were collected, and the related factors of suicide ideation of AIDS patients were analyzed by univariate and multivariate unconditional logistic regression. Results: Among the 300 AIDS patients, 88 (29.33%) had suicidal ideation and 212 (70.67%) had no suicidal ideation; Anxiety, depression, history of attempted suicide, less CD4+T lymphocyte count, stronger self-esteem, lower social support, and stronger discrimination perception were independent risk factors for suicide ideation in AIDS patients (P<0.05). Conclusion: The probability of suicide ideation in AIDS patients is quite high, which is closely related to anxiety, depression, history of attempted suicide, CD4+T lymphocyte count, self-esteem, social support and discrimination perception. Specific prevention and treatment measures can be given according to relevant factors in clinical practice. Keywords: Interpersonal theory of suicide; Acquired immunodeficiency syndrome; Suicidal ideation; Related factors